Chronic active non-lethal human-type tuberculosis in a high royal Bavarian officer of Napoleonic times-a mummy study. - Andreas G Nerlich; Sonja M Kirchhoff; Stephanie Panzer; Christine Lehn; Beatrice E Bachmeier; Birgit Bayer; Katja Anslinger; Pascale Röcker; Oliver K Peschel (PLoS ONE)
In paleopathology, morphological and molecular evidence for infection by mycobacteria of the M. tuberculosis complex (MTC) is frequently associated with early death. In the present report, we describe a multidisciplinary study of a well-preserved mummy from Napoleonic times with a long-standing tuberculous infection by M. tuberculosis senso stricto who died at the age of 88 years of focal and non-MTB related bronchopneumonia. The well-preserved natural mummy of the Royal Bavarian General, Count Heinrich LII Reuss-Köstritz (1763-1851 CE), was extensively investigated by macro- and histomorphology, whole body CT scans and organ radiography, various molecular tissue analyses, including stable isotope analysis and molecular genetic tests. We identified signs for a long-standing, but terminally inactive pulmonary tuberculosis, tuberculous destruction of the second lumbar vertebral body, and a large tuberculous abscess in the right (retroperitoneal) psoas region (a cold abscess). This cold abscess harboured an active tuberculous infection as evidenced by histological and molecular tests. Radiological and histological analysis further revealed extensive arteriosclerosis with (non-obliterating) coronary and significant carotid arteriosclerosis, healthy bone tissue without evidence of age-related osteopenia, evidence for diffuse idiopathic skeletal hyperostosis and mild osteoarthrosis of few joints. This suggests excellent living conditions correlating well with his diet indicated by stable isotope results and literary evidence. Despite the clear evidence of a tuberculous cold abscess with bacterioscopic and molecular proof for a persisting MTC infection of a human-type M. tuberculosis strain, we can exclude the chronic MTC infection as cause of death. The detection of MTC in historic individuals should therefore be interpreted with great caution and include further data, such as their nutritional status.